Current Research and Perspective of the Role of Microwave Ablation in Managing Hepatocellular Carcinoma: A Systematic Review - Zhaoduo Jin,; Chai Nien Foo,; Xin Jet Din,; Quan Fu Gan,; Chye Wah Yu,; Yong Cao,; Naing Soe Yan, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Hepatocellular carcinoma is one of the most common leading causes of death especially in Asia. While the main pillars of intervention for hepatocellular carcinoma in Malaysia are chemotherapy, radiotherapy, immunotherapy and surgical resection of tumors, these interventions presence with many weaknesses. Microwave ablation is one of the latest technologies which possess a shorter ablation time compared to other thermal ablation techniques, as well as lesser post-operative complications when compared to surgical resection of tumors. Hence, the aim of this review is to compile available research articles pertaining to microwave ablation in hepatocellular carcinoma. An extensive search was done in PubMed Central, BioMed Central, ScienceDirect, and Wiley Online Library from 2019 to 2024 to identify original research on the use of microwave ablation in managing hepatocellular carcinoma. During the search, 10 articles met our inclusion criteria where eight of the studies were conducted in Asia itself. All studies yield favorable results on the use of microwave ablation. However, more studies should be conducted in comparing microwave ablation with the current trend such as stem cells therapy. Overall, we concluded that microwave ablation is most suitable to be catered for the high number of patient load and lack of hospital bed in Malaysian government hospital considering its shorter ablation time and lesser complications.